2021
DOI: 10.1002/qj.4037
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic processes contributing to the intensification of anomalously strong North Atlantic jets

Abstract: Anomalously strong North Atlantic jets, defined in this study as jets with wind speeds exceeding 100 m·s−1, are notable due to their potential to induce high‐impact weather. This study examines the kinematic processes that contribute to the intensification of anomalously strong North Atlantic jets, as well as the variability in those processes across a large number of events. Anomalously strong jets are objectively identified during September–May 1979–2018 within the Climate Forecast System Reanalysis and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
(132 reference statements)
0
4
0
Order By: Relevance
“…Previous case‐studies have also identified that negative PV experiences an anti‐cyclonic advection path when in close proximity to the jet stream (Blanchard et al., 2021; Oertel et al., 2020). Winters (2021) proposed that different components of the wind field, such as the ageostrophic non‐divergent component of the wind, can play a more dominant role over the irrotational wind field in determining the advection of low values of PV toward the jet stream. Our case‐study illustrates that negative PV arises from regions of strong irrotational wind‐fields; however, it would be interesting to expand upon this research further by identifying whether different components of the wind field become more significant as the negative PV is advected further away from the center of the irrotational wind field.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous case‐studies have also identified that negative PV experiences an anti‐cyclonic advection path when in close proximity to the jet stream (Blanchard et al., 2021; Oertel et al., 2020). Winters (2021) proposed that different components of the wind field, such as the ageostrophic non‐divergent component of the wind, can play a more dominant role over the irrotational wind field in determining the advection of low values of PV toward the jet stream. Our case‐study illustrates that negative PV arises from regions of strong irrotational wind‐fields; however, it would be interesting to expand upon this research further by identifying whether different components of the wind field become more significant as the negative PV is advected further away from the center of the irrotational wind field.…”
Section: Discussionmentioning
confidence: 99%
“…The metric used in Equation is phase independent and tracks packets of error that propagate in a wave‐like motion (i.e., RWPs) and specifically pertains to rotational error due to the use of the streamfunction term. This makes the metric useful for identifying the initial development of forecast error onto the jet stream, which is dominated by non‐divergent wind flow (Keyser & Johnson, 1984; Winters, 2021). WAEψ=12][ψex2+ψey2ψe)(2ψex2+2ψey2 $WA{E}_{\psi }=\frac{1}{2}\left[{\left(\frac{\partial {\psi }_{e}}{\partial x}\right)}^{2}+{\left(\frac{\partial {\psi }_{e}}{\partial y}\right)}^{2}-{\psi }_{e}\left(\frac{{\partial }^{2}{\psi }_{e}}{\partial {x}^{2}}+\frac{{\partial }^{2}{\psi }_{e}}{\partial {y}^{2}}\right)\right]$ …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in understanding cross‐isentropic vertical mass transport in extratropical cyclones indicates that diabatic processes play a significant role in shaping the upper level PV gradient more often than was assumed previously (Wernli and Davies, 1997; Davies and Didone, 2013; Methven, 2015; Pfahl et al ., 2015; Saffin et al ., 2021). Recently, Winters (2021) adopted an Eulerian approach by using PV frontogenesis to study the evolution of extreme jets and identified diabatic processes as important contributors to jet streak formation. These findings are a prelude to a Lagrangian study of PV frontogenesis, because the integrated effects of adiabatic and diabatic tendencies along the flow are crucial for understanding the state of the instantaneous PV gradient field along the jet.…”
Section: Introductionmentioning
confidence: 99%